Deep Brain Stimulation: A Potential Treatment for Dementia in Alzheimer's Disease (AD) and Parkinson's Disease Dementia (PDD) - Lv, Qing; Du, Ailian; Wei, Wenshi; Li, Yuanyuan; Liu, Gailing; Wang, Xiao Ping (Frontiers in Neuroscience, 2018)
Damage to memory circuits may lead to dementia symptoms in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD). Recently, deep brain stimulation (DBS) has been shown to be a novel means of memory neuromodulation when critical nodes in the memory circuit are targeted, such as the nucleus basalis of Meynert (NBM) and fornix. Potential memory improvements have been observed after DBS in patients with AD and PDD. DBS for the treatment of AD and PDD may be feasible and safe, but it is still preliminary. In this review, we explore the potential role of DBS for the treatment of dementia symptoms in AD and PDD. Firstly, we discuss memory circuits linked to AD and PDD. Secondly, we summarize clinical trials and case reports on NBM or fornix stimulation in AD or PDD patients and discuss the outcomes and limitations of these studies. Finally, we discuss the challenges and future of DBS for the treatment of AD and PDD. We include the latest research results from Gratwicke et al. (2017) and compare them with the results of previous relevant studies, and this would be a worthy update of the literature on DBS for dementia. In addition, we hypothesize that the differences between AD and PDD may ultimately lead to different results following DBS treatment.